Dieta e dispersão de sementes por lobo-guará (Chrysocyon brachyurus) em área de Cerrado antropizado, na região de Mogi-Guaçu - SP - Ercolin, Gabriele Arthur (Universidade Federal de São Carlos, 2026)
The maned wolf (Chrysocyon brachyurus), largest canid in South America, is classified as a vulnerable species, mainly due to habitat loss and alteration, hunting pressure, risk of diseases transmitted by domestic animals and road kills. Feeding primarily on small vertebrates, insects and fruits, especially of the “wolf fruit”, the maned wolf plays an important role as a seed disperser, being essential for the maintenance of the ecosystems in which it occurs. Therefore, this study aimed to analyze the feeding ecology of this species, describing quantitatively and qualitatively its diet and its role as a seed disperser in a human-modified landscape at Fazenda Campininha in Mogi Guaçu. A total of 109 scats were collected, resulting in 27 identified taxa, with Solanum lycocarpum, Poaceae and Cricetidae showing the highest frequencies of occurrence among samples. Germination test was conducted with S. lycocarpum seeds, showing a germination rate of 6% for seeds recovered from scats, whereas seeds obtained directly from fruits showed a germination rate of 2.5%, in addition to a lower mean germination time (MGT) and a higher germination speed index (GSI) for ingested seeds. Seed viability was assessed using the tetrazolium test, indicating an average viability of 90% for seeds recovered from scats. These results highlight the importance of the maned wolf in seed dispersal and the provision of ecological services, emphasizing the need for the conservation of the species to ensure the functioning of Cerrado ecosystems.
Diet and seed dispersal by the maned wolf (Chrysocyon brachyurus) in an anthropized Cerrado area, in the Mogi-Guaçu region - SP
Keywords: Conservação; Lobo-guará; Cerrado; Ecologia alimentar; Conservation; Maned wolf; Savannah; Feeding ecology; CIENCIAS BIOLOGICAS::ZOOLOGIA; 15. Vida Terrestre